A homologous-targeting "nanoconverter" with variable size for deep tumor penetration and immunotherapy. Issue 9 (23rd February 2021) - Cong, Cong; Jiaxin, Bian; Liu, Xiaokang; Zhang, Xinyue; Fu, Yihan; Li, Zhuo; Xu, Zichuang; Wei, Shipan; Wang, Desong; Gao, Dawei
Abstract : Schematic of the fabrication of PTX/PDA@M-C6 for deep penetration, photothermal response release, specific tumor apoptosis and immunotherapy. Abstract : Tumor-associated immunosuppression, as a key barrier, prevents immunotherapy-resistant tumors. In this study, an ingenious "nanoconverter" was designed to convert immunosuppression into immunoactivation, which was a C6-ceramide (C6)-modified tumor cytomembrane-coated polydopamine-paclitaxel system (PTX/PDA@M-C6). The co-administration of C6-ceramide and tumor cytomembrane changed an adaptive immune state to an activation state, which induced a robust antigen presentation ability of tumor-infiltrating dendritic cells to activate T1 helper cells and cytotoxic T lymphocytes. Meanwhile, C6-ceramide regulated the phenotype of macrophages via the reactive oxygen species pathway, which resulted in the conversion of M2-like macrophages by infiltration within tumors into M2-like macrophages, and therefore, M2-like macrophage-mediated immunosuppression was weakened distinctly. The "nanoconverter"-mediated conversion process upregulated the expression of related immune factors including interleukin-12, interleukin-6, tumor necrosis factor-α and interferon-γ and executed positive anti-tumor effects. In addition, under the protection of tumor-homologous cytomembrane, the "nanoconverter" exhibited excellent delivery efficiency (23.22%), and subsequently, accumulated special structural "nanoconverter" could break down into smaller nanoparticles for deep penetration into the tumor tissue under a NIR laser. Ultimately, chemo/thermal therapy-assisted immunotherapy completely eliminated the tumors of tumor-bearing mice, and a potent memory response relying on effector memory T cells still persisted to protect against tumor relapse after the end of treatment. The "nanoconverter" serves as a promising nanodrug delivery system for the conversion of immunosuppression and enhanced chemo/thermal therapy. Therefore, the highly cumulative "nanoconverter" has great potential for promoting the effect and clinical application of immunotherapy.